2007
DOI: 10.1002/anie.200701028
|View full text |Cite
|
Sign up to set email alerts
|

K7B7Si39, a Borosilicide with the Clathrate I Structure

Abstract: Including boron: K7B7Si39 (see structure; large spheres: K, small spheres: Si, B) is the first clathrate I compound with boron atoms. With 9.952(1) Å, the borosilicide exhibits the smallest lattice parameter among all intermetallic clathrate I compounds. The composition is in agreement with the Zintl rule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
66
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 19 publications
4
66
0
Order By: Relevance
“…23) A constant carrier relaxation time approximation was assumed so that the Seebeck coefficient could be obtained independent of the carrier relaxation time, while the electrical conductivity and electronic thermal conductivity could be obtained as carrier-relaxation-timedependent quantities. Carrier doping was treated as a shift in the Fermi level on the basis of the band structure of the X 8 Y 8 Si 38 . Such a treatment is called a "rigid-band approximation".…”
Section: Computational Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…23) A constant carrier relaxation time approximation was assumed so that the Seebeck coefficient could be obtained independent of the carrier relaxation time, while the electrical conductivity and electronic thermal conductivity could be obtained as carrier-relaxation-timedependent quantities. Carrier doping was treated as a shift in the Fermi level on the basis of the band structure of the X 8 Y 8 Si 38 . Such a treatment is called a "rigid-band approximation".…”
Section: Computational Proceduresmentioning
confidence: 99%
“…However, as the band structure is expected to severely change in heavy doping, the rigid-band approximation would fail when Fermi-level is located more than 0.1 eV into the band edge. 24) We also checked the applicability of rigid-band approximation to the present Si-clathrate system, from the analysis on band structures of one electron and/or hole doped Si 46 and K 8 Ga 8 Si 38 . It was confirmed that changes of band structure could be characterized only by shifting the Fermi level, which was moved about 0.1 eV inside bands.…”
Section: Computational Proceduresmentioning
confidence: 99%
See 3 more Smart Citations